Dynamic stall of an airfoil with different mounting angle of gurney flap. Issue 7 (12th June 2020) - Masdari, Mehran; Mousavi, Milad; Tahani, Mojtaba
Abstract : Purpose: One of the best methods to improve wind turbine aerodynamic performance is modification of the blade's airfoil. The purpose of this paper is to investigate the effects of gurney flap geometry and its oscillation parameters on the pitching NACA0012 airfoil. Design/methodology/approach: This numerical solution has been carried out for different cases of gurney flap mounting angles, heights, reduced frequencies and oscillation amplitudes, then the results were compared to each other. The finite volume method was used for the discretization of the governing equations, and the PISO algorithm was used to solve the equations. Also, the "SST" was adopted as the turbulence model in the simulation. Findings: In this paper, the different parameters of gurney flap were investigated. The results showed that the best range of gurney flap height are between 1 and 3.2% of chord and the best ratio of lifting to drag coefficient is achieved in gurney flap with an angle of 90° relative to the chord direction. The dynamic stall angle of the airfoil with gurney flap decreases were compared to without gurney flap. Earlier LEV formation can be one of the main reasons for decreasing the dynamic stall angle of the airfoil with gurney flap. Increasing the reduced frequency and oscillation amplitude causes rising of maximum lift coefficient and consequently lift curve slope. Moreover, gurney flap with mounting angle has a lower hinge moment than the gurney flap without mounting angle but with the same vertical axis length. So, there is more complexity in structural design concerning the gurney flap without mounting angle. Practical implications: Improving aerodynamic efficiency of airfoils is vital for obtaining more output power in VAWTs. Gurney flaps are one of the best mechanisms to increase the aerodynamic performance of the airfoil and increases the efficiency of VAWTs. Originality/value: Investigating the hinge moment on the connection point of the airfoil, gurney flap and try to compare the gurney flap with and without angle.